Biodiversity, ecosystem functioning, and human wellbeing an ecological and economic perspective - Naeem, Shahid (Oxford biology., 2009)
Biodiversity change is one of the most controversial and high profile areas of ecological research. This text provides an in-depth evaluation of the science and its implications and applications to some of the most pressing environmental issues facing humans today.